Artificial intelligence and machine learning for women's health issues - Gupta, Meenu (Professor of computer science); Hemanth, D. Jude (Academic Press, 2024)
Artificial Intelligence and Machine Learning for Women's Health Issues discusses the applications, challenges, and solutions that machine learning can bring to women's health challenges. The book illustrates advanced, innovative techniques, frameworks, concepts, and methodologies of machine learning which enhance the future healthcare system. This book's primary focus is on women's health issues and machine learning's role in providing solutions to these challenges, providing novel ideas for feasible implementation. It also provides an early-stage analysis for early diagnosis of women's health issues.